College Science Clubs, as a Social Responsibility strategy in Tabasco - Arias Herrera, Josúe; Medina Morales, Gladys del Carmen (Emerging Trends in Education, 2022)
The College Science Clubs (CUC) are a multidisciplinary group of integrated students to give experimental or demonstrative science workshops with the aim of bringing young people and children closer to scientific work and promoting their interest in science. A strategy of social responsibility, carried out by the Universidad Juárez Autónoma de Tabasco through the CUC. This strategy began with the clubs in 2014 with the teaching of scientific dissemination workshops to students of upper secondary education in the state of Tabasco. Descriptive data of a case study on his work of scientific dissemination are presented. The study covers a period of four years in which 140 workshops were given, in 30 schools of three different subsystems of the 17 municipalities of the State, to tres mil 400 students. With this, the UJAT sensitizes an important sector of society to take an interest in scientific activity, at a crucial stage in deciding their professional future. This boost to scientific vocations is a primary act of Social Responsibility in the face of the challenges facing the country.